Reliability in urban freight distribution: a markovian approach (2014)
A key element in assessing reliability in urban freight distribution (UFD) is the probability density function (PDF) of the variables that characterize the performance of the distribution routes. This article presents a method for modeling the PDF with an approach based on the Markov models, under the assumption that the present status of reliability of a route depends only on its immediate previous state. Currently, the PDF is obtained directly from the field, therefore an analytical model that provides certainty to the analysis is essential. The results are applicable both to the design of routes and operation of the same process. The originality of this work is based on the development of a methodological procedure to assess the reliability of the components of a path, complementary to current methodologies to calculate network reliability.